Relationships between fungal endophytes and wood-rot fungi in wood of Platanus acerifolia in urban environments - Robles, Carolina Analía (2015)
Urban forests, which are highly valuable for the urban environment, include trees from city streets that might be susceptible to wood-decay fungi. Fungal endophytes can colonize healthy plant tissues without causing external disease symptoms in standing trees. In this study, the diversity of endophytes isolated from wood of Platanus acerifolia (Aiton) Willd. from Buenos Aires, Argentina, is described and related to different levels of urban disturbance, tree age, and presence of wood-decay basidiomycetes. Samples were obtained from 28 asymptomatic trees (1643 wood core fragments) and 75 symptomatic trees (1516 wood sample fragments) from four sites with different levels of human disturbance. Fungal isolates were morphologically identified, and potential wood-decay isolates were phylogenetically analyzed. Twenty-seven endophytic taxa, including five basidiomycetes, were identified. The multivariate analysis suggested that the endophyte community of wood is highly influenced by the level of urban disturbance, followed by tree age and presence of potential pathogenic basidiomycetes.